2021
DOI: 10.1021/acs.langmuir.1c03097
|View full text |Cite
|
Sign up to set email alerts
|

Evaporation Dynamics of Surfactant-Laden Droplets on a Superhydrophobic Surface: Influence of Surfactant Concentration

Abstract: Surfactant-laden sessile droplet evaporation plays a crucial role in a variety of omnipresent natural and technological applications, such as drying, coating, spray, and inkjet printing. Surfactant molecules can adsorb easily on interfaces and, hence, destructively ruin the useful gas-trapping wetting state (i.e., Cassie–Baxter, CB) of a drop on superhydrophobic (SH) surfaces. However, the influence of surfactant adsorption or concentration on evaporation modes has been rarely investigated so far. Here, we in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 65 publications
2
6
0
Order By: Relevance
“…By definition, a hydrophilic surface is characterized by a sessile water droplet’s contact angle (CA) on a flat surface being less than 90°. In contrast, a hydrophobic (or superhydrophobic, SH) surface exhibits a water droplet’s CA greater than 90° (150° with a small CA hysteresis). , To quantify the wettability influence of SiO 2 nanoparticles, we measured the CA of a Milli-Q water droplet on three surfaces: a flat silica (SiO 2 ) wafer, a flat silica wafer coated with octadecyltrichlorosilane (OTS) solution (purity >90%), and a flat silica wafer coated with hydrophobic SiO 2 nanoparticles. Using a water droplet, the corresponding CA measurements are 43 (±1)°, 99 (±1)°, and 147 (±3)°, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By definition, a hydrophilic surface is characterized by a sessile water droplet’s contact angle (CA) on a flat surface being less than 90°. In contrast, a hydrophobic (or superhydrophobic, SH) surface exhibits a water droplet’s CA greater than 90° (150° with a small CA hysteresis). , To quantify the wettability influence of SiO 2 nanoparticles, we measured the CA of a Milli-Q water droplet on three surfaces: a flat silica (SiO 2 ) wafer, a flat silica wafer coated with octadecyltrichlorosilane (OTS) solution (purity >90%), and a flat silica wafer coated with hydrophobic SiO 2 nanoparticles. Using a water droplet, the corresponding CA measurements are 43 (±1)°, 99 (±1)°, and 147 (±3)°, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Droplet impact studies have recently demonstrated that heat transfer between the droplet and surface crucially influences droplet hydrodynamics and the subsequent impact outcome. , Despite the known variations in thermal conductivity between nanofluids and their base fluids, experimental studies focusing on nanofluid droplet dynamics upon heated surfaces remain largely unexplored. For nanofluid droplet impacts on such surfaces, two primary regimes can be characterized based on surface temperature ( T s ): the non-boiling and boiling regimes.…”
Section: Introductionmentioning
confidence: 99%
“…All experiments were performed under ambient temperature (22 °C) at 1 atm and relative humidity of 16 ± 1%. Details regarding the experimental setup and image analysis can be found in our previous papers reporting the initial wetting states of water and surfactant-laden drops, whereas we focus on the static and dynamic wetting of ionic liquids here.…”
Section: Methodsmentioning
confidence: 99%
“…To better understand SH breakdown, the wetting transition has been extensively studied in quasi-static configurations, such as in an evaporating droplet (McHale et al 2005;Jung & Bhushan 2007;Tsai et al 2010;Bussonnière et al 2017), with surfactant additives (Shardt et al 2019;Aldhaleai & Tsai 2022), under different drop volumes (Yoshimitsu et al 2002) and pressures (Lafuma & Quéré 2003) or in dynamic situations, e.g. drop impact (Bartolo et al 2006) or under surface vibrations (Bormashenko et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…2017), with surfactant additives (Shardt et al. 2019; Aldhaleai & Tsai 2022), under different drop volumes (Yoshimitsu et al. 2002) and pressures (Lafuma & Quéré 2003) or in dynamic situations, e.g.…”
Section: Introductionmentioning
confidence: 99%